2020
DOI: 10.3389/fphar.2020.01249
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Modulates the Gut Microbiota and Inflammation to Protect Against Diabetic Nephropathy in Mice

Abstract: Oral administration of resveratrol is able to ameliorate the progression of diabetic nephropathy (DN); however, its mechanisms of action remain unclear. Recent evidence suggested that the gut microbiota is involved in the metabolism therapeutics. In the current study, we sought to determine whether the anti-DN effects of resveratrol are mediated through modulation of the gut microbiota using the genetic db/db mouse model of DN. We demonstrate that resveratrol treatment of db/db mice relieves a series of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 39 publications
(49 reference statements)
3
97
0
Order By: Relevance
“…It is generally believed that gut microbiota triggers innate and adaptive immunity and maintains the stability of the intestine ( Hooper and Macpherson, 2010 ). In previous studies about Inflammatory Bowel Disease and Diabetic Nephropathy, the transplantation of fecal microbiota from RSV gavage mice directly affected the intestinal inflammation and gut barrier of the recipient mice ( Alrafas et al, 2019 ; Cai et al, 2020 ), indicating the RSV might alter the intestinal inflammation by gut microbiota. We also observed reductions in liver inflammation and oxidative stress after RSV treatment.…”
Section: Discussionmentioning
confidence: 91%
“…It is generally believed that gut microbiota triggers innate and adaptive immunity and maintains the stability of the intestine ( Hooper and Macpherson, 2010 ). In previous studies about Inflammatory Bowel Disease and Diabetic Nephropathy, the transplantation of fecal microbiota from RSV gavage mice directly affected the intestinal inflammation and gut barrier of the recipient mice ( Alrafas et al, 2019 ; Cai et al, 2020 ), indicating the RSV might alter the intestinal inflammation by gut microbiota. We also observed reductions in liver inflammation and oxidative stress after RSV treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Resveratrol is capable of modifying miR-21 expression in diverse cell culture models. Experiments employing the culture of U251 cells, cultured with resveratrol for 12 h, reduced miR-21 expression, and this was followed by the decrease in the generation of proinflammatory transcription factor NF-κB [ 114 ]. The reduction of miR-21 could have a beneficial effect on the progression of osteoporosis.…”
Section: Modifying the Microbiota/mirnas Axis: A New Approach To Omentioning
confidence: 99%
“…Additionally, the ratio Bacteroidetes / Firmicutes is higher in db/db mice, than on C57Bl/6J mice [ 205 ]. On the other hand, family Muribaculaceae is reduced in db/db mice by 8 months of age [ 209 ], while other studies have reported that genus Rikenella (family Rikenellaceae ) is increased in db/db mice by 6 months of age [ 210 ]. It also seems that genera Paraprevotella and Alloprevotella , (family Prevotellaceae ) are increased in db/db mice by 6 months of age, while the genus Alloprevotella decreases by 8 months of age [ 209 , 211 ].…”
Section: Diet Inflammation and Gut Microbiota In T2dm Modelsmentioning
confidence: 99%
“…This phylum (family Prevotellaceae ) is also decreased in E4FAD and db/db mice at 8 months of age [ 209 , 211 , 248 ]. Actinobacteria (family Coriobacteriaceae ) has been reported to be increased both in APP/PS1 [ 132 ] and in db/db mice [ 205 ], while the Bacteroidaceae family seems to be less abundant in different AD and T2DM preclinical models [ 90 , 132 , 134 , 204 , 209 , 210 , 211 , 257 ]. Nevertheless, other studies have reported increases in the Bacteroidaceae family, both in AD [ 119 ] and T2DM animals [ 204 , 209 , 210 , 211 ].…”
Section: Common Microbiota Alterations In Ad T2dm and Mixed Preclmentioning
confidence: 99%
See 1 more Smart Citation